Child Rights to Guardianship A Comparative Study in International, Islamic and Libyan Laws - Mesrati, Ali Omar Ali. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book examines how local cultures affect the interpretation of international human rights law. This book explores the Islamic legal system in its approach to the concept of guardianship and, more specifically, the approach of the Libyan legal system through a study of existing legislation and Libyan High Court (LHC) interpretation as revealed in its decisions. This book aims to show how the cultural background affects the interpretation of international human rights in domestic legal systems. This book makes a worthy contribution to promoting greater understanding of the cultural dimensions in operation in both the formulation and particularly the application of international law in Libya as elsewhere. This is an area of research which is, as a whole, one worthy of further development and examination. The book includes case analysis of important Libyan High Court rulings which have been gathered by the author and officially translated, analysed, and discussed from the three lenses namely; Libyan Law, Islamic Law, and International Law. In turn, this book is the first of its kind and unique in the field of Islamic and International Law. This book also includes detailed analysis of the correspondence between the Libyan High Court and the UN Committee on the Rights of the Child. Further, this book provides solutions and comprehensive and practical recommendations that satisfy both International standards and local Islamic and Libyan culture. This is an ever evolving and a current area of interest internationally, this unique book enriches the field and continues the conversation and provides practical sustainable solutions. .
Introduction -- The 'Best Interests of the Child' in the Context of Guardianship Under International Law -- 'The Best Interests of the Child' Under Islamic Law -- 'The Best Interests of the Child' Under the Libyan Legal System -- Conclusion.
Keywords: Civil law; Domestic relations; International law; Civil procedure; Private international law; Conflict of laws; Comparative law; Mediation; Dispute resolution (Law).; Arbitration (Administrative law).; Civil Law; Family Law; Public International Law; Civil Procedure Law; Private International Law, International and Foreign Law, Comparative Law; Dispute Resolution, Mediation, Arbitration